Nuansa Konvensional dalam Perbankan Syariah - M. Nazori Madjid (NALAR FIQH: Jurnal Hukum Islam, 2011)
This article is an evaluation of the Islamic bankings performance is currently being assessed are not much different from conventional bank. Many record given by the researchers and the general public against the Islamic bank about sharia supervisory board, core bisnis of Islamic bank, and reviewers closer look at product of Islamic banking.